Role of gut-brain axis in neurodevelopmental impairment of necrotizing enterocolitis - Wang, Yu; Hang, Chengcheng; Hu, Jun; Li, Chen; Zhan, Canyang; Pan, Jiarong; Yuan, Tianming (Frontiers in Neuroscience, 2023)
Necrotizing enterocolitis (NEC) is a common gastrointestinal disease of preterm infants with high morbidity and mortality. In survivors of NEC, one of the leading causes of long-term morbidity is the development of severe neurocognitive injury. The exact pathogenesis of neurodevelopmental delay in NEC remains unknown, but microbiota is considered to have dramatic effects on the development and function of the host brain via the gut-brain axis. In this review, we discuss the characteristics of microbiota of NEC, the impaired neurological outcomes, and the role of the complex interplay between the intestinal microbiota and brain to influence neurodevelopment in NEC. The increasing knowledge of microbial-host interactions has the potential to generate novel therapies for manipulating brain development in the future.